The Effect of Problem-Based Learning Methods and the Use of Kahoot Game Applications on Student Learning Outcomes in Grade IX Civic Education - Sitorus, Acnes Monica; Saragih, Sepriandison; Banjarnahor, Daulat Nathanael (CV Putra Publisher, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) method and the use of the Kahoot application on students’ learning outcomes in Civic Education (PKn) subject for ninth-grade students of UPTD SMP Negeri 1 Pematangsiantar in the 2025/2026 academic year. The background of this research is based on the low learning interest and student engagement caused by monotonous and conventional teaching methods. This study employed a quantitative approach with a Quasi-Experimental design using the Pre-test Post-test Control Group method. The population consisted of 343 ninth-grade students, with a sample of 61 students divided into experimental and control classes. The research instrument was a multiple-choice test that had been validated and tested for reliability using SPSS. Data were analyzed using normality test, N-Gain test, and t-test. The findings indicate that the implementation of the Problem Based Learning method and the use of the Kahoot application have a significant effect on students’ learning outcomes. These strategies improve students’ motivation, engagement, and comprehension, resulting in better learning achievements compared to conventional methods. This research is expected to serve as a reference for teachers in selecting innovative teaching methods and media to enhance the quality of the learning process.